Analisis pengaruh bauran pemasaran dan citra merek terhadap keputusan memilih sekolah dengan word of mouth sebagai variabel intervening - Suriyanto Suriyanto (Journal of Business & Banking, 2025)
The increasing public need for quality Islamic Education creates a competitive climate fot private educational institutions, thereby encouraging research in the field of education marketing. This research aims to analyze the influencs of the service marketing mix (product, place, people, and process), brand image, on the decision of parents/ guardians in choosing an Islamic boarding school (SMP) with word of mputh as an intervening variable. The population in this study were all parents/guardinas of TQT Madinatul Quran Junior High School Depok City. The sampe studied was 176 respondents whose children were in grades 7 to 9. The analysis technique used was descriptive analysis and SEM (structural Equation Modelling) with Lisrel version 8.80. The results of statistical test show that the relationship between marketing mic and brand image directly influences word of mouth. Other results show a direct relationship that influences the decision to choose a school, namely the brand image and word of mouth varibles. Brand image through word of mouth has a significant influence on the decision to choose school. Marketing mix variables do not have an influence either directly or through word of mouth on the decision to choose school.